The Relationship Between Level of Knowledge and Behaviors of COVID-19 Prevention among Indonesian Population - Weni Widya Shari (Jurnal Ners, 2021)
Introduction: Currently, there are no specific drugs to cure COVID-19, so it is an important strategy to be implemented in the community to increase knowledge and preventive behavior in order to prevent transmission. The purpose of this study was to see the relationship between the level of knowledge and preventive behavior against COVID-19 among Indonesian population.Methods: This study used an analytical method with a cross-sectional design. Samples were taken from the people of Depok City as many as 406 people. The independent variable was knowledge and the dependent variable was preventive behavior. The instruments used were questionnaires on the characteristics of the respondents and knowledge and behavior with online questionnaire via Google Forms. The sampling technique was non-probability sampling with a consecutive sampling method. Data analysis used descriptive analysis test, Chi-square and correlative hypothesis test.Results: The results showed that respondents have good knowledge (56.9%) and good prevention behavior (75.9%). The largest source of information about COVID-19 respondents was from Television News (84.4%). There was a significant relationship between the level of knowledge and preventive behavior toward COVID-19 (p=0.000). Moreover, there is a significant relationship between age (p=0.000), gender (p=0.000), education level (p=0.000) and work status (p=0.016) with knowledge.Conclusion:The findings suggest that the local government should initiate an innovative program of health education focusing on knowledge and preventive behavior toward COVID-19 at a community level. The strategies to combat COVID-19 will require community involvement to control and prevent the disease outbreak.